Examining our Conditionings: A Session with Postgraduate Students on Critical Pedagogy - Mathai, Sindhu (Voices of Teachers and Teacher Educators, 2021)
The National Education Policy (2020) calls upon schools to develop caring, inclusive communities. Looking inward and confronting our thoughts and biases is an important step in this journey. While reading Paulo Freire’s classic work Pedagogy of the Oppressed (2005), as well as the conversation between Freire and Macedo on critical pedagogy (Freire and Macedo, 2003), I was struck by how meaningful this was as pedagogic practice. Freire’s exhortation to educators and students to be conscious of their individual subjectivities while being part of social practice is even more significant with the current crises of different kinds: social, economic, political, religious, etc., all over the world. We are alerted as educators, also to our conditionings from our growing up years, and our internalisation of norms, often without our own knowledge. Unpacking these conditionings therefore, with a group of potential educators and teachers, seemed essential. This paper analyses a classroom exercise, which was part of a discussion on critical pedagogy with students in a curriculum studies core course within an MA Education programme. I had asked students to note down and bring up for discussion, ways in which each of them felt ‘conditioned’. What emerged was a fascinating narrative cutting across multiple topics and themes: caste, religion, region, physical appearance, bodily functions, public and private schools, values, the idea of success, dominant school subjects, gendered professions, class consciousness, media messages, assessment structures and failure, growing up, mental health, hierarchical structures, etc. It helped students re-look and articulate what they had taken for granted, as problems, which need to be re-thought and to be eventually acted upon.